THE RELATIONSHIP BETWEEN PREVENTIVE ATTITUDES AND THE INCIDENCE OF EXTENDED SPECTRUM BETA-LACTAMASE (ESBL)-PRODUCING ENTEROBACTERIACEAE CARRIERS AMONG HEALTHCARE WORKERS IN HOSPITALS - Nuranisa, Aulia; Hestiyani, Rani Afifah Nur; Karunia Ning Widhi, Anriani Puspita; Hidayah, Arfi Nurul; Krisniawati, Nia (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Infections caused by Extended Spectrum Beta-Lactamase (ESBL)-producing Enterobacteriaceae have become a serious health issue, particularly in hospital environments. Gram-negative bacteria such as Escherichia coli and Klebsiella pneumoniae are able to produce ESBL, making them resistant to various beta-lactam antibiotics and complicating infection treatment. The spread of ESBL-producing bacteria is often associated with suboptimal infection prevention practices in healthcare facilities, particularly among healthcare workers who may act as vectors in transmittinghese pathogens. This study aimed to determine the relationship between attitudes and the incidence of ESBL-producing Enterobacteriaceae carriers among healthcare workers in hospitals. This research was conducted using secondary data. Data were analyzed using Fisher Exact test. The result showed no significant relationship between attitudes and the incidence of ESBL carriage, as indicated a p-value of 1.000. The conclusion there was no relationship between attitude and the incidence of ESBL-producing Enterobacteriaceae carriage among healthcare workers at RSI Banjarnegara.